2014
DOI: 10.1371/journal.pone.0088111
|View full text |Cite
|
Sign up to set email alerts
|

Shared Gene Structures and Clusters of Mutually Exclusive Spliced Exons within the Metazoan Muscle Myosin Heavy Chain Genes

Abstract: Multicellular animals possess two to three different types of muscle tissues. Striated muscles have considerable ultrastructural similarity and contain a core set of proteins including the muscle myosin heavy chain (Mhc) protein. The ATPase activity of this myosin motor protein largely dictates muscle performance at the molecular level. Two different solutions to adjusting myosin properties to different muscle subtypes have been identified so far: Vertebrates and nematodes contain many independent differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 58 publications
2
20
0
Order By: Relevance
“…In contrast to cassette exons and micro‐exons, which tend to be located in surface loops and intrinsically disordered regions instead of folded domains (Buljan et al , 2012; Ellis et al , 2012; Irimia et al , 2014), all MXEs, whose protein structures have been analysed, are embedded within folded structural domains as has been shown for, for example, DSCAM (Meijers et al , 2007), H2AFY (Kustatscher et al , 2005), the myosin motor domain (Kollmar & Hatje, 2014) and SLC25A3 (Tress et al , 2017a). As we have shown in the beginning, there is also a subset of 73 MXEs not showing any sequence homology (“annotated no similarity”).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast to cassette exons and micro‐exons, which tend to be located in surface loops and intrinsically disordered regions instead of folded domains (Buljan et al , 2012; Ellis et al , 2012; Irimia et al , 2014), all MXEs, whose protein structures have been analysed, are embedded within folded structural domains as has been shown for, for example, DSCAM (Meijers et al , 2007), H2AFY (Kustatscher et al , 2005), the myosin motor domain (Kollmar & Hatje, 2014) and SLC25A3 (Tress et al , 2017a). As we have shown in the beginning, there is also a subset of 73 MXEs not showing any sequence homology (“annotated no similarity”).…”
Section: Resultsmentioning
confidence: 98%
“…SCN1A ] with the Drosophila calcium channel cac gene and not the orthologous sodium channel para gene). At least for muscle myosin heavy chain genes it could be demonstrated that Drosophila already lost several MXE clusters compared to, for example, Daphnia pulex (crustacean) and lophotrochozoans (Kollmar & Hatje, 2014) and that the evolutionary history of the MXEs within each cluster is remarkably complex with multiple independent exon duplications and losses (Odronitz & Kollmar, 2008). Thus, detailed studies including more bilaterian and non‐bilaterian taxa would be necessary to finally conclude convergent or divergent evolution for each of the human and Drosophila MXE clusters.…”
Section: Resultsmentioning
confidence: 99%
“…duplication of the class-3 and class-7 myosins in the ancestor of arthropods and insects, respectively) and in (according to current sequence data) single species (e.g. duplication of muscle myosin heavy chain genes in the leech Helobdella robusta and the owl limpet Lottia gigantea [ 48 ]; see the myosin inventory table at CyMoBase for more examples). Together, these gene duplications indicate extensive subfunctionalization (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In many species, the myosin gene shows clusters of mutually exclusive exons (MXEs) that are alternatively spliced to give different protein isoforms (Bernstein et al 1986 ; Wassenberg et al 1987 ; George et al 1989 ; Odronitz and Kollmar 2008 ; Kollmar and Hatje 2014 ). Evolutionary analysis shows eleven potential MXE clusters that code for specific regions of the molecule, ten within the S1 myosin head (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Evolutionary analysis shows eleven potential MXE clusters that code for specific regions of the molecule, ten within the S1 myosin head (Fig. 1 e) and one within the helical rod domain (Odronitz and Kollmar 2008 ; Kollmar and Hatje 2014 ). The ancestral arthropod gene is predicted to be intron rich, with 42 exons that are typically short (Kollmar and Hatje 2014 ).…”
Section: Introductionmentioning
confidence: 99%